2015
DOI: 10.1007/s13204-015-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment on haemotology, biochemical and histopathological alterations of silver nanoparticles-exposed freshwater fish Labeo rohita

Abstract: The increasing use of nano based-products induces the potential hazards from their manufacture, transportation, waste disposal and management processes. In this report, we emphasized the acute toxicity of silver nanoparticles (AgNPs) using freshwater fish Labeo rohita as an aquatic animal model. The AgNPs were synthesized using chemical reduction method and the formation of AgNPs was monitored by UV-Visible spectroscopy analysis. The functional groups, crystaline nature and morphological characterizations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(59 citation statements)
references
References 35 publications
9
49
0
Order By: Relevance
“…Histopathological changes found in the rainbow trout muscle tissue exposed to aqueous AgNPs and CuNPs suspensions were similar to those observed in previous experiments with NPs (Salem, Kenney, Rexroad & Yao, 2010;Al-Bairuty, Shaw, Handy & Henry, 2013;Girial, Krishnakumar, Poornima, Fayaz & Kalaichelvan, 2015). The increase of the intercellular area in muscle tissue, observed in this study was also found in other studies on effects of pesticides and heavy metals on fish (Capkin, Terzi, Boran, Yandi & Altinok, 2010;Patnaik Howrelia, Mathews & Selvanayagam, 2011;Bhuvaneshwari, Padmanaban & Babu Rajendran, 2015;Rajkumar, Kanipandian & Thirumurugan, 2016). In the CuNPs group numerously occurring shrinked acidophilic muscle bounds exhibited unspecific dystrophic changes.…”
Section: Discussionsupporting
confidence: 88%
“…Histopathological changes found in the rainbow trout muscle tissue exposed to aqueous AgNPs and CuNPs suspensions were similar to those observed in previous experiments with NPs (Salem, Kenney, Rexroad & Yao, 2010;Al-Bairuty, Shaw, Handy & Henry, 2013;Girial, Krishnakumar, Poornima, Fayaz & Kalaichelvan, 2015). The increase of the intercellular area in muscle tissue, observed in this study was also found in other studies on effects of pesticides and heavy metals on fish (Capkin, Terzi, Boran, Yandi & Altinok, 2010;Patnaik Howrelia, Mathews & Selvanayagam, 2011;Bhuvaneshwari, Padmanaban & Babu Rajendran, 2015;Rajkumar, Kanipandian & Thirumurugan, 2016). In the CuNPs group numerously occurring shrinked acidophilic muscle bounds exhibited unspecific dystrophic changes.…”
Section: Discussionsupporting
confidence: 88%
“…4). Figure 5 shows that the selected-area electron diffraction (SAED) pattern of green-synthesized AgNPs confirms the crystalline (fcc) nature of the silver nanoparticles (Rajkumar et al 2015).…”
Section: Xrd Analysismentioning
confidence: 73%
“…Treatment with nanoparticle shows disruption, deterioration of muscle fiber characterized by fissures and breaks in the muscle fibers. Inflammation in the fibre was observed in AgNP's treated Labeo rohita [55], the disintegration of myofibrils along with pyknotic nuclei was evident in the treated group suggesting the toxic effect of green synthesized silver nanoparticles.…”
Section: Discussionmentioning
confidence: 94%
“…Disruption of ATPase enzyme inhibits the uptake of Na + and ClGills are responsible for regulating the exchange of salt and water even a slight structural damage can render a fish very vulnerable to osmoregulatory as well as respiratory difficulties. AgNPs treated fishes show lamellae fusion and aneurism formation in gills and enlargement of liposomes leading to vascular degeneration of liver [55]. Necrosis was observed in the secondary lamellae of the rainbow trout treated with AgNPs [56].…”
Section: Discussionmentioning
confidence: 99%